ANALYSIS OF THE DETERMINANTS OF FAMILY ECONOMIC RESILIENCE IN LUWU RAYA WITH SOCIAL SUPPORT AS A MODERATING VARIABLE - Nur Fitriani Pirman; Fasiha; Ishak (Referensi Islamika: Jurnal Studi Islam, 2026)
This study aims to analyze the influence of Islamic financial literacy, access to Islamic financing, and entrepreneurial motivation on Family Economic Resilience in Luwu Raya with social support as a moderating variable. This study employs a quantitative approach using primary data collected through a questionnaire distributed to single parents who are micro and small business owners in Luwu Raya. The data were analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with the assistance of the SmartPLS 4 software to test both direct effects and moderating effects among the variables. The results of the study indicate that entrepreneurial motivation has a positive and significant effect on family economic resilience, whereas Islamic financial literacy and access to Islamic microfinance do not show a significant effect. Social support also does not show a significant moderating effect. These findings suggest that individual internal factors play a more dominant role than external factors in strengthening family economic resilience. This study highlights the importance of strengthening entrepreneurial motivation in supporting family economic resilience among single mothers who are micro-entrepreneurs. This study expands the body of research on Family Economic Resilience by examining the relationship between Islamic financial literacy, access to Islamic microfinance, entrepreneurial motivation, and social support in the context of single mothers who are microentrepreneurs.